The role of working hours, work environment and physical leisure activity on the need for recovery following a day's work among UK white-water raft guides: A within-subjects multilevel approach. (March 2016) - Wilson, Iain; McDermott, Hilary; Munir, Fehmidah
Abstract: Background: White-water raft guides are a growing workforce of the outdoor sector but little is known about how the working environment, workload and physical leisure activity impacts on the need for occupational recovery (the desire to replenish internal resources and recuperate in the time immediately following work) of those working in this physically demanding occupation. Methods: Longitudinal data were collected across an eight month working season at three month intervals. Multilevel analyses tested the within-subject associations between work environment, hours worked and physical leisure activity had on the need for recovery. Results: Working longer across the working season and participating in more physical leisure activity were directly associated with a lower need for occupational recovery. Furthermore, working on natural rivers significantly reduced the need for recovery experienced compared to work on man-made courses. This was regardless of the number of hours of worked in these environments. Discussion: Physical leisure activity may provide a distraction from work, allowing employees to replenish their physical and psychological energy, thus protecting themselves against work-related fatigue. The findings also expand upon the previous literature identifying that working in a natural environment reduces the risk of experiencing work-related fatigue. Highlights: Hours of raft guiding was associated with a lower need for recovery across time. A greater amount of physical activity was associated with lower levels of fatigue. Workers in a natural environment as opposed to man-made experienced less fatigue. Work environment did not alter relationship between hours worked and fatigue.